Investigations of the Genetic aspects of the mixed Lymphocyte culture reaction in Southern Africa - du Toit, Ernette D (Adolescent Health Research Institute, 2020)
The genetic relationship between the serologically detectable antigens of the HLA-A and B loci and the mixed lymphocyte culture (MLC) reaction is of utmost importance in the understanding of histocompatibility. From the literature it appeared that neither the HLA-A, B genotype nor the MLC reaction is the complete answer to donorrecipient selection in organ transplantation. This study was therefore initiated in June 1971 in an attempt to clarify the problem. It is inherent in a project of this nature that much time is spent in collecting samples from donors in diverse areas. Most experiments had to be repeated two or three times, therefore some of the problems we set out to resolve were clarified by other workers before we were able to complete our investigations.